Cloud Standby - Eine Methode zur Vorhaltung eines Notfallsystems in der Cloud - Lenk, Alexander (KIT Scientific Publishing, 2019)
Small and Medium size Companies (SME) are facing threats on a daily basis. Even if 94% of German SMEs are regularly backing up their data, only 50% use a different datacenter provider for protecting critical business processes with a disaster recovery system. The goal of this thesis is it to describe a new method for providing a disaster recovery system within the Cloud.